2007
DOI: 10.3171/spi.2007.6.3.229
|View full text |Cite
|
Sign up to set email alerts
|

Split–spinous process laminotomy and discectomy for degenerative lumbar spinal stenosis: a preliminary report

Abstract: Object The authors evaluated a new minimally invasive spinal surgery technique to correct degenerative lumbar spinal stenosis involving a split–spinous process laminotomy and discectomy (also known as the “Marmot operation”). Methods This prospective study randomized 70 patients with lumbar stenosis to undergo either a Marmot operation (40 patients), or a conventional laminectomy (30 patients), with or w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
112
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(116 citation statements)
references
References 45 publications
(31 reference statements)
2
112
1
1
Order By: Relevance
“…Review of trial registries revealed no other ongoing or unpublished trials. We subdivided studies evaluating posterior decompressive techniques into unilateral laminotomy for bilateral decompression [4,24,25], bilateral laminotomy [2][3][4]26] and split-spinous process laminotomy [27][28][29][30] to ensure clinical homogeneity.…”
Section: Results Of the Searchmentioning
confidence: 99%
See 4 more Smart Citations
“…Review of trial registries revealed no other ongoing or unpublished trials. We subdivided studies evaluating posterior decompressive techniques into unilateral laminotomy for bilateral decompression [4,24,25], bilateral laminotomy [2][3][4]26] and split-spinous process laminotomy [27][28][29][30] to ensure clinical homogeneity.…”
Section: Results Of the Searchmentioning
confidence: 99%
“…Decisive arguments were the inclusion of concomitant intertransverse arthrodesis (in 12 out of 67 participants) and concomitant discectomy (in 7 out of 67 participants) by Postacchini et al [3], and concomitant discectomy (in 44 out of 70 participants) by Cho et al [27]. Concomitant discectomy was not among the predefined exclusion criteria of this review, but the exceptionally high rate of concomitant discectomy by Cho et al compared with no …”
Section: Included Studiesmentioning
confidence: 94%
See 3 more Smart Citations